The importance of studying military terms (Eurasian Journal of Learning and Academic Teaching, 2021)
The military term is defined as "a stable unit of synthetics of an analytical nomination assigned to the relevant concept in the conceptual and functional system of a certain sphere in profession in the meaning regulated by its definition". This article discusses the importance of studying military terms.